2017
DOI: 10.1016/j.gca.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The boron and lithium isotopic composition of mid-ocean ridge basalts and the mantle

Abstract: The global set of samples investigated here were produced at various degrees of partial melting and in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
162
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 230 publications
(173 citation statements)
references
References 175 publications
10
162
1
Order By: Relevance
“…Today, the best estimate for the d 11 B of uncontaminated MORB is −7.1 ± 0.9‰, and it is homogenous in boron isotopes on the level of current analytical precision and accuracy. It is further concluded that assimilation of seawater or seawater-altered materials produces elevated d 11 B values as observed in a number of MORB glass samples (Chaussidon and Jambon 1994;Marschall et al 2017; Fig. 8.1).…”
Section: Mid-ocean Ridge Basaltsmentioning
confidence: 59%
See 4 more Smart Citations
“…Today, the best estimate for the d 11 B of uncontaminated MORB is −7.1 ± 0.9‰, and it is homogenous in boron isotopes on the level of current analytical precision and accuracy. It is further concluded that assimilation of seawater or seawater-altered materials produces elevated d 11 B values as observed in a number of MORB glass samples (Chaussidon and Jambon 1994;Marschall et al 2017; Fig. 8.1).…”
Section: Mid-ocean Ridge Basaltsmentioning
confidence: 59%
“…The authors use a d 11 B reference value of −3 ± 3‰ for MORB-source mantle and interpret all observed values higher than that as due to assimilation of altered Hawai'ian crust into the magma (Kobayashi et al 2004). Values lower than −6‰ are taken as evidence for deeply recycled ancient subducted crust; however, there are no data that are significantly lower than the more recently suggested d 11 B value for the MORB-source mantle (−7.1 ± 0.9‰; Marschall et al 2017), suggesting that all data may be explained by melts derived from mantle without an unusual B isotopic composition, and that the observed range may be due to various degrees of assimilation of altered crust. Kobayashi et al (2004) also report a wide range of Li isotopes in the melt inclusions, but these would have to be revisited in the light of kinetic isotope fractionation during diffusion of Li in and out of the melt inclusions after entrapment.…”
Section: St Helena Mcdonald Afarmentioning
confidence: 70%
See 3 more Smart Citations